2011
DOI: 10.1523/jneurosci.6394-10.2011
|View full text |Cite
|
Sign up to set email alerts
|

Estrogen Shapes Dopamine-Dependent Cognitive Processes: Implications for Women's Health

Abstract: Summary The prefrontal cortex (PFC) is exquisitely sensitive to its neurochemical environment. Minor fluctuations in cortical dopamine (DA) can profoundly alter working memory, a PFC-dependent cognitive function that supports an array of essential human behaviors. Dopamine’s action in the PFC follows an inverted U-shaped curve, where an optimal DA level results in maximal function and both insufficient or excessive DA impairs PFC function. In animals, 17-β estradiol (the major estrogen in most mammals, referre… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

21
303
3

Year Published

2014
2014
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 322 publications
(327 citation statements)
references
References 82 publications
21
303
3
Order By: Relevance
“…In participants scoring high in cognitive disorganisation, high estradiol levels resulted in decreased confidence in false memories, while for participants scoring low on cognitive disorganisation, confidence in false memories was greater with higher estradiol levels. When considering meta-memory as a cognitive control process, the present data suggests that the beneficial effect of estradiol on cognitive control (Hjelmervik et al, 2012;Jacobs and D'Esposito, 2011;Keenan et al, 2001) might be specific to participants with high cognitive disorganisation, at least within the domain of memory.…”
Section: Estradiol Reduces False Memory Confidence In Highly Schizotymentioning
confidence: 82%
See 1 more Smart Citation
“…In participants scoring high in cognitive disorganisation, high estradiol levels resulted in decreased confidence in false memories, while for participants scoring low on cognitive disorganisation, confidence in false memories was greater with higher estradiol levels. When considering meta-memory as a cognitive control process, the present data suggests that the beneficial effect of estradiol on cognitive control (Hjelmervik et al, 2012;Jacobs and D'Esposito, 2011;Keenan et al, 2001) might be specific to participants with high cognitive disorganisation, at least within the domain of memory.…”
Section: Estradiol Reduces False Memory Confidence In Highly Schizotymentioning
confidence: 82%
“…However, it is currently unclear whether the effect of estrogen on memory occurs because of direct effects of estrogen on memory or rather via hormonal effects on memory control functions, such as meta-memory processes (Colzato et al, 2010). Indeed, it has been suggested that the enhancing effect of estrogen is particularly evident during tasks that demand a high level of (meta-) cognitive control, (Hjelmervik et al, 2012;Jacobs and D'Esposito, 2011). Given that meta-memory processes are conceptually comparable to cognitive control processes, it follows that meta-memory abilities should be enhanced under high estrogen conditions.…”
Section: Introductionmentioning
confidence: 99%
“…From these findings we conclude that the transmission of reward signals to the PFC, in particular its dopaminergic component, is largely dependent on the gonadal hormone milieu, and E2 regulates dopamine availability mainly through the modulation of intracellular signaling pathways [55,58]. The tuning of dopamine levels has particular importance since dopamine effects follow a U-shaped dose-response curve in the PFC [57,59,60].…”
Section: Estrogen-dependent Modulation Of the Mesocortical System Invmentioning
confidence: 88%
“…Proper executive functioning depends on the neurochemical environment of executive regions including the dorsolateral prefrontal cortex (DLPFC), the region of the prefrontal cortex (PFC) critical for attention and working memory (Arnsten and Jin, 2014). PFC function has been characterized as an inverted U-shaped curve such that optimal executive function (EF) depends on a balance of factors including baseline monoaminergic and glutamatergic function (Arnsten and Jin, 2014) as well as hormonal status (Jacobs and D'Esposito, 2011). In such a model, a decrease in estradiol levels during menopause could cause executive difficulties in women whose genetics or previous life experiences make them susceptible to such a cognitive decline (Culpepper, 2015;Kudielka et al, 2009;Shanmugan and Epperson, 2014) (Figure 1).…”
Section: Introductionmentioning
confidence: 99%
“…In women who metabolize dopamine more quickly, low estradiol levels result in improper PFC activation during working memory tasks (Jacobs and D'Esposito, 2011). Preclinical models have suggested estradiol modulation of glutamatergic function may be an additional mechanism by which estradiol loss induces changes in cognition.…”
Section: Introductionmentioning
confidence: 99%